Pandemic diagrams: for a taxonomy of ongoing thinking (Publicatio UEPG: Ciências Sociais Aplicadas, 2021)
This article proposes a taxonomy of global intellectual production on the Sars-Cov-2 (Covid-19) pandemic. Based on a qualitative and quantitative approach, along with the methods of content analysis and conjunctural analysis, we analyzed a textual corpus composed of 52 documents on the pandemic, written by 33 active intellectuals, with recognized international impact and originating from the most different areas of knowledge of the Human and Social Sciences. This analysis advances the hypothesis that the pandemic event constitutes a focus of attraction for contemporary thinking, in such a way that a taxonomy of the analyzed corpus would epistemologically collaborate to establish the directions in which contemporary thinking moves in the pandemic context.